Produk Interior Kantor Berbasis Budaya Lokal Suku Dayak Benuaq Kalimantan Timur - Windy Novelin Medica Putri; Laksmi Kusuma Wardani; Grace Setiati Kattu (Intra, 2020)
Benuaq Dayak is one of the Dayak tribes in East Kalimantan, and has a variety of arts, one of which is Ulap Doyo. Ulap Doyo is the art of weaving cloth, the material used is from the Doyo plant with the Latin name Curculigo Latifolia, the plant fiber is taken then spun and woven into a Ulap doyo fabric. Ulap doyo weaving was used an idea for the transformation of the design of furniture sets and as for the materials the desaigners used a specific material which is recommanded for the furniture is Bengkirai wood. The method used is empathize,define,ideate, prototyping and testing. This design has the concept of form of weaving that is parallel, forming lines and arranged in a modern contemporary style and the resulting products are desk, portable drawers, arm chairs, and sofa. This interior product is not only a modern design that reflects the continent of Dayak culture but is also strong and durable for long-term use.